Two new species of the genus Mataeopsephus Waterhouse, 1876 (Coleoptera: Psephenidae) from Guizhou, China - Jiang, Ri-Xin; Chen, Xiang-Sheng (Zootaxa, 2024)
Two new species of the genus Mataeopsephus Waterhous are described: M. fanjingshanus sp. nov. and M. zhaomingzhii sp. nov. both from Guizhou Province, China. A revised key to the species of all known Mataeopsephus species is provided.